PENGARUH MODEL ROLE PLAYING TERHADAP KETERAMPILAN MEMBACA BAHASA INDONESIA (PENELITIAN QUASI EXPERIMENT DI KELAS III SDN 020 LENGKONG BESAR KOTA BANDUNG) - Erika Nabila Nursolihat; Dindin MZM; Arifin Ahmad (STKIP Subang, 2023)
The study aims to determine whether there is an influence on the use of Role Playing models in reading skills Indonesian elementary school and differences in students' reading skills before and after the Role Playing model is given. The subjects of this study were class III-A students as an experimental class and class III-B as a control class at SDN 020 Lengkong Besar Bandung. Types of quasi-experimental research with data collection techniques are pretes, posttes and non-test techniques. The results showed: (i) There is an influence on the reading skills of students, which can be seen based on the average data of posttes results which show higher scores than the average pretes scores, with an average posttes score of 83.33 while the average pretes score is 57.08. The results showed: (i) There is an influence on the reading skills of students, which can be seen based on the average data of posttes results which show higher scores than the average pretes scores, with an average posttes score of 83.33 while the average pretes score is 57.08. As the end of the study, the advice that can be given to school principals is expected to make these results as material for learning evaluation. Teachers are expected to be able to choose and develop appropriate and varied learning models and methods. For students, it is expected to be more active in learning. For further researchers, it is expected to be able to conduct further research by developing other aspects in it that affect the reading skills of students.